Crop straw utilization and field burning in Northern region of Ghana. (10th July 2020) - Seglah, Patience Afi; Wang, Yajing; Wang, Hongyan; Bi, Yuyun; Zhou, Ke; Wang, Ying; Wang, Huan; Feng, Xinxin
Abstract: Efficient utilization of crop straw is a determining factor for cleaner production and sustainable development in Ghana's agricultural sector. However, extensive field burning of crops straw is hampering the effective utilization of straw resources in the Northern region of Ghana. The aim of this research was to identify rural households' crops straw utilization methods and investigate the occurrence as well as effects of crops straw burning. Cross-sectional data collected from 384 farmer households' in Yendi municipality, Saboba and Tatale-Sanguli districts in the Northern region of Ghana were analyzed with Statistical Package of Social Sciences (SPSS). The total crop yield for major cereals and legumes produced was 1.29 kton with a total crop straw yield of 3.05 kton. Cereals straw contributed the highest yield percentage of 56.4% while legume straw contribution was 43.6%. About 1.23kton (40.3%) of straws from major cereals and legumes were utilized for different purposes such as returning to the field to enrich the soil, fodder for livestock, cooking fuel, sale and other traditional purposes. The remaining 1.82kton (59.7%) of crop straws were burnt on the field. The percentages of straw burnt on the field for each crop were 77.6% for maize, 58.6% for sorghum, 56.5% groundnut, 49.7% for millet, 47.4% cowpea, 42.2% for rice and 41.4% for soybean. Farming and farm size are the key influencing factors that affect straw burning. Open field burning of straws caused a decline in yield for about 65.7% of respondents. The present findings indicates that utilization of crop straw in the Northern region of Ghana is poorly practiced and needs to be encouraged because of its associated benefits. Government of Ghana needs to develop appropriate policies and legislative measures to encourage effective utilization of straw and prohibit field burning of straws. Highlights: Different straw utilization methods are identified in the study area. Straw utilization methods identified are poorly practiced. Large proportions of straw are burnt on the farm by farmers or hunters. Straw burning has negative effects on human and the environment. Farming and farm size are determinant for future occurrence of burning.